Proceedings of the Third Padang International Conference on Economics Education, Economics, Business and Management, Accounting 2019
DOI: 10.2991/piceeba-19.2019.54
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Organizational Justice, Trust in Bosses and Job Satisfaction on Employee Performance at PT. PLN (Persero) Main Unit of West Sumatra Region

Abstract: The most important thing in an organization is performance. Performance is the goal of the organization. Performance is a measure of the success of an organization in carrying out business processes. In this article we have developed the influence of Organizational Justice, Trust in Boss and Job Satisfaction with Performance From relevant theories and research conducted by several researchers about the relationship between these variables in previous studies, we argue that Organizational Justice has a signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 14 publications
1
1
0
1
Order By: Relevance
“…These results prove that if the organization applies justice to all employees, a sense of fasting will arise from the employee. This is also in line with the results of research conducted by Kristanto, (2015); Sarianti et al, (2017); (Ali, 2016); (Tangka, et al, 2017); (Aditya, 2019); (Juarsah, et al, 2019) showing organizational justice has a positive effect on employee performance.…”
Section: Discussionsupporting
confidence: 87%
“…These results prove that if the organization applies justice to all employees, a sense of fasting will arise from the employee. This is also in line with the results of research conducted by Kristanto, (2015); Sarianti et al, (2017); (Ali, 2016); (Tangka, et al, 2017); (Aditya, 2019); (Juarsah, et al, 2019) showing organizational justice has a positive effect on employee performance.…”
Section: Discussionsupporting
confidence: 87%
“…It significantly impacts employee retention by fostering perceptions of fairness in policies, procedures, and reward systems, which are crucial for maintaining a conducive work environment [14,15]. Studies have shown that organizational justice not only enhances job satisfaction, commitment, and performance but also reduces turnover intention by improving the organization-employee relationship [16,17,18]. Furthermore, organizational justice extends its influence to affect employees' affective commitment, job satisfaction levels, and organizational citizenship behavior, emphasizing its significance in driving positive organizational outcomes [19,20].…”
Section: Review Of Related Literaturementioning
confidence: 99%
“…Besarnya pengaruh keadilan organisasi, kompensasi, lingkungan kerja, dan motivasi intrinsik adalah sebesar 38,6%, sisanya 61.4 dijelaskan oleh variabel yang tidak tercakup dalam penelitian ini. Hasil pengujian menunjukkan H1 diterima, hal ini sesuai penelitian yang dilakukan oleh (Juarsah et al, 2019) menunjukan bahwa keadilan organisasi berpengaruh signifikan terhadap kepuasan kerja karyawan. Temuan ini membuktikan bahwa kepuasan kerja dapat ditingkatkan sehingga karyawan akan merasa betah dan nyaman ditempat kerja.…”
Section: Pengujian Hipotesisunclassified